Elúszó pénzek az egészségügyben - Esettanulmány egy évekig tartó büntetőeljárásról - Kiss, Tamás (Debreceni Jogi Műhely, 2011)
In the financing of the Public Health System, it has a particular significance on the one hand that those obligated do pay the required taxes and levies (Health contribution) in order, and on the other, to use the already available resources only to the purpose that laws allow.The institutes that provide public health care services maintain themselves in part or on the whole on the support of the central budget or the Health Insurance Fund. The criteria listed by Law indicate and limit on what the institutes may spend the amount of funds received, which areas should they strive to develop.The question arises that how other charges, such as expenses related to the quality management system, can fit into this well-defined scope. In my opinion, it would be possible to avoid the giving away of unrealistically large amounts of money to semi-, or fully illegal businesses with greater circumspection, because otherwise too many sources are distracted from Health Care.